HER2-low breast cancer. Diagnostics, treatment and its adverse events - Bartkowiak, Hanna; Grubski, Damian; Ziarnik, Kacper; Nadolny, Filip; Jabłoński, Jędrzej; Kania, Martyna; Adamowska, Agnieszka; Śniatała, Alicja (Journal of Education, Health and Sport, 2024)
Introduction: Breast cancer is one of the most commonly diagnosed malignant tumors among women worldwide. HER2 receptor is a protein that plays a role in cell growth, division, and repair. Approximately 50% of HER2 –negative breast cancers express low levels of HER2 receptors. HER2-low breast cancer is a newly characterized subtype of breast cancers that express low levels of HER2 receptor but do not meet the criteria for HER2 positivity and HER2 negative with SCORE - 0 in immunohistochemistry. Recent studies have discovered that HER2-targeted therapies can be effective even at low HER2 expression levels. Aim of study: The purpose of this review was to increase awareness of HER2- low breast cancer. The objective was also to underscore the importance of detecting low and very low expression of HER2 receptors. The other goal of this project is to raise awareness of potential new directions in oncological treatments including antibody–drug conjugates. Materials and methods: The review was based on the analysis of materials collected in the „Pubmed” and Google Scholar databases. The search was performed using the keywords: „HER2-low breast cancer”, trastuzumab deruxtecan antibody–drug conjugates”, „HER2-low diagnostic algorithm”. Conclusion: The results of the DESTINY - Breast04 study shows that trastuzumab-deruxtecan significantly improved both progression-free survival and overall survival among all patients including hormone-positive patients cohort compared to chemotherapy. While trastuzumab-deruxtecan is highly effective, it does come with specific safety considerations that necessitate close monitoring.